La era del litio: un desafío socioambiental y una necesidad de concientización en Costa Rica - Álvarez-Huete, Warren (2026)
The lithium era represents a rapidly expanding battery market, growing from USD 30 billion in 2017 to an estimated USD 100 billion in 2025. While this growth is crucial for reducing dependence on fossil fuels, lithium extraction is currently unsustainable. Using a mixed-methods approach that included a literature review and a Google Forms survey, 172 individuals were surveyed regarding the use and management of devices that rely on this technology. Of the respondents, 81% were between 17 and 26 years of age. A total of 447 instances of lithium-based device use were recorded, and the findings revealed a significant lack of awareness regarding the environmental impacts associated with improper battery handling and disposal. Promoting a circular economy is therefore essential, as is integrating acritical perspective into the education of engineers in training to address this emerging challenge.